(untitled) (Bangladesh Journal of Pharmacology, 2015)
Assessing the antidiabetic potential of Acalypha alnifolia is the main objective of the present study. Two doses of leaf extracts were treated with streptozotocin-induced diabetic rats for 21 days. The glucose level, insulin level, plasma lipids, total protein, electrolytes and plasma enzymes were monitored. The acetone extract of 400 mg/kg had potentiated to diminish the glucose and lipid level as well as other diabetic complications. Internal structures of pancreas were studied by histopathological sections and insulin expression was also observed by immunohistochemical study. Though the extracts having good antioxidant capability it might have to reduce the beta cell destruction or helps to repair it. The result of the toxicity analysis, histopathology and insulin expression supports the acetone extract. The present study attesting the antidiabetic properties of A. alnifolia hence this plant would be focused and taken for cultivation leads to add in human diet for getting therapeutic benefit.